Axillary lymphangioma that developed following COVID-19 vaccination: a case report - Soichiro Sasa; Hiroaki Inoue; Tomohiro Inui; Naoki Miyamoto; Mariko Aoyama; Kazumasa Okumura; Hiroaki Toba; Takahiro Yoshida; Miki Tezuka; Chieko Hirose; Yasuyo Saijo; Hisanori Uehara; et al. (Surgical Case Reports)
Abstract Background Extensive vaccination programs are being implemented worldwide for coronavirus disease 2019 (COVID-19). With the spread of vaccination, swelling of the lymph nodes after vaccination is frequently seen. We encountered a patient who developed left axillary lymphadenoma following vaccine administration. Case presentation The patient was a Japanese woman in her 80 s who had previously undergone surgery for right breast cancer. She received two injections of the Pfizer-BioNTech COVID-19 vaccine in her left arm. Approximately 3 months later, she complained of left axillary swelling, and imaging resulted in a diagnosis of left axillary lymphangioma. In accordance with the patient’s wishes, we performed axillary mass resection. The pathological diagnosis was lymphangioma. Conclusion Our examination findings indicated that congestion of the axillary lymph vessels might have been caused by upper-arm injections of the COVID-19 vaccine.